Similarity-based visualization of large image collections. (July 2015) - Wang, Chaoli; Reese, John P; Zhang, Huan; Tao, Jun; Gu, Yi; Ma, Jun; Nemiroff, Robert J
Effective techniques for organizing and visualizing large image collections are in growing demand as visual search gets increasingly popular. Targeting an online astronomy archive with thousands of images, we present our solution for image search and clustering based on the evaluation of image similarity using both visual and textual information. Time-consuming image similarity computation is accelerated using graphics processing unit. To lay out images, we introduce iMap, a treemap-based representation for visualizing and navigating image search and clustering results. iMap not only makes effective use of available display area to arrange images but also maintains stable update when images are inserted or removed during the query. We also develop an embedded visualization that integrates image tags for in-place search refinement. To show the effectiveness of our approach, we demonstrate experimental results, compare our iMap layout with a force-directed layout, and conduct a comparative user study. As a potential tool for astronomy education and outreach, we deploy our iMap to a large tiled display of nearly 50 million pixels.